Use of local wisdom (purpusage) through heart-to-heart communication in settling of social conflicts in Karo, North Sumatra Indonesia - Lestari, Puji; Kertamukti, Rama; Ruliana, Poppy
Refusal of refugee relocation policy due to the eruption of Mount Sinabung from the community members in Lingga Village, Karo Regency, in North Sumatra Province has created social conflict. This study aims to find a model of social conflict management through heart-to-heart local wisdom, known as communication purpusage in Karo, North Sumatra. This research uses a qualitative approach in order to further explore and understand the process of heart to heart basis of communication and local wisdom. Data collection techniques used in this research are observation and in-depth interviews on research subjects, more specifically the background of the conflict, the parties involved in the conflict, the impacts of the conflict, and the solutions adopted. The results of this study show that a heart-to-heart communication model in the Karo culture through a process of runggu (communication for peace) produces local wisdom of purpusage that effectively resolves the conflict. This research contributes in offering a new concept of heart-to-heart communication for resolving social conflicts using a local wisdom called purpusage. Heart-to-heart communication among all conflicting parties has created a sincere communication attitude, which tends to accept the situation, willingness to overcome the conflict, and a strong desire to live peacefully. Village Community of Lingga Karo in North Sumatra has agreed to emphasize on heart to heart communication because it is rooted in their local culture named runggu and purpusage. This research recommends that local wisdom can effectively be used as an effort to resolve social conflicts.